PENCEGAHAN BULLYING PADA ANAK USIA DINI DI KALIMANTAN SELATAN - RIZKI NOOR HAIDA (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2021)
This study aims to determine the various types of Bullying that occur in early childhood, to distinguish the perpetrators as well as the psychological perpetrators of Bullying, to describe children's interference with Bullying and Bullying prevention programs from various early childhood sites. This research is in-depth (a case study of three elements synergizing to provide information, namely actors, place and activity). This type of research is intensive and comprehensive in studying a phenomenon. Data were collected through observation, interviews, and documentation. Based on the results and discussion of research on preventing Bullying in early childhood in South Kalimantan, it shows that the type of Bullying that occurs is in the form of verbal actions such as mocking, making fun of and insulting fellow friends, physically in the form of pushing, hitting and kicking. Children's intervention towards Bullying still does not fully understand and cannot judge a good or bad deed, so that Bullying prevention programs against children from various sites through play activities make children feel more comfortable and can provide positive information in managing the program (plan evaluate), and the existence of the Parent's Club program which is an association of parents in helping the smooth implementation of the learning process at the institution.